Penerapan Pembelajaran Pendidikan Agama Islam (PAI) Berbasis Higher Order Thinking Skills (Hots) - Zulfa Indah Pratiwi; Dewi Maharani (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2020)
This research based on the conventional learning method used by PAI teachers which caused the lack of critical thinking among students and thus affects the low quality of education. The purpose of this research is to explain the need of Higher Order Thinking Skills (HOTS) learning methods to increase the students’ critical thinking capacity. This research used the qualitative method with w descriptive approach and took place at SMA Dharma Karya UT, South Tangerang. Main sources of data of this research are the teachers of Islamic education, 11th grade students, and the head of school. However, the secondary source of data which is used are from books, journals, and other thesis. This research also used documentary sources which consisted of previous thesis results, RPP documents, 11th grade students’ daily test documents, photo, and audio. The data collection techniques consisted of observation, interview, and documentation. However, in the implementation, there are three aspects to growing HOTS among students. First, analyzing, operating by inspecting the application of the method is students are able to critical thinking and problem solving about obedient behavior. Second, evaluating, performed by evaluating the method that was previously used is when students are given inappropriate statement by teacher and students expressed their arguments related to obedient behavior, competitive in kindness and work ethic. Third, creating, observed from the effects after learning the Islamic Education subject.